2016
DOI: 10.1021/acs.joc.5b02907
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of N-Tosylacetimidates/Acetimidamides onto Arynes via [2 + 2] Cycloaddition

Abstract: A novel insertion reaction of N-tosylacetimidates and N-tosylacetimidamides onto arynes via a benzocyclobutene intermediate followed by ring cleavage is developed to afford o-benzylbenzoic acid derivatives in good yields. Interestingly, the use of cyclic 2-sulfonyliminoindolines provided two distinct products such as azepanimines via [2 + 2] cycloaddition and indolamines via protonation based on solvent medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…We have recently taken advantage of Stolz’s contributions in benzyne chemistry for the total synthesis of natural products . Also, we were successful in adding imidate functionality to benzynes to generate disubstituted aryl systems with minimal effort . We were exploring to develop a strategy for easy entry to 2-substituted benzofurans enroute the total synthesis of natural products and bioactive molecules (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently taken advantage of Stolz’s contributions in benzyne chemistry for the total synthesis of natural products . Also, we were successful in adding imidate functionality to benzynes to generate disubstituted aryl systems with minimal effort . We were exploring to develop a strategy for easy entry to 2-substituted benzofurans enroute the total synthesis of natural products and bioactive molecules (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…7 Also, we were successful in adding imidate functionality to benzynes to generate disubstituted aryl systems with minimal effort. 8 We were exploring to develop a strategy for easy entry to 2-substituted benzofurans enroute the total synthesis of natural products and bioactive molecules (Figure 1). 9 In 2017, Miyabe et al have recently reported the synthesis of dihydrobenzofurans and benzofurans from arynes, wherein o-QM reacts with diethyl 2-chloromalonate and diethylzinc at −40 to −60 °C in DMF as a solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, the same reaction was realized with cyclic 2sulfonyliminoindolines 319 affords the two different products such as azepanimines 321 through [2 + 2] cycloaddition and indolamines 322 through protonation (Scheme 51). [105] Ramtohul and Blackburn have reported a mild approach to the preparation of N-substituted α,α-disubstituted benzocyclobutene amino ester and isoquinoline 3-carboxylates using benzyne chemistry. The reaction of 2-amidoacrylate esters 323 with benzyne precursors 102 in the presence of CsF generated a mixture of substituted isoquinolines 325 as major products and α,α-disubstituted benzocyclobutenes 324 as minor products (Scheme 52).…”
Section: Miscellaneousmentioning
confidence: 99%
“…In recognition of increasingly strict conservational and regulatory imperatives, 1 much attention is now focused upon innovative functionalization methodologies 2 that are applicable to more readily available and economic feedstocks, 3 while simultaneously emphasizing environmentally friendly, especially metal-free, reaction conditions. 4 To these ends, there has been encouraging progress recently in the application of site-selective C(sp 2 )–C(sp 3 ) and C(sp 2 )–C(sp 2 ) cleavage strategies, 5 despite the comparatively high bond dissociation energy of most unstrained C–C bonds and the formidable challenges posed by discriminating amongst otherwise chemically equivalent C–C bonds 6 ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%